Impact of Adverse Events on Urban Air Quality: the Example of the Rome Fire - Nicoletta Lotrecchiano; Daniele Sofia (Chemical Engineering Transactions)
Adverse events such as fires pose a significant threat to air quality in urban areas, with both immediate and long-term impacts on public health and the environment. This study examines the effects of a major fire that occurred in Rome in 2024, affecting an industrial area and resulting in a substantial release of atmospheric pollutants. Using monitoring sensors and dispersion models, we measured the increase in fine particulate matter (PM2.5 and PM10) during and after the incident. The collected data were compared with standard air quality levels, highlighting a critical exceedance of safety thresholds. Furthermore, the study evaluates the effectiveness of the measures taken to contain pollution and reduce public exposure, proposing preventive and management solutions to minimize the impact of future events. The results emphasize the need to improve response strategies to such phenomena and to strengthen the alert system to ensure better protection of air quality and urban health.